Prospects for the development of creation of combined alternative energy converters (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The paper presents the results of research work on the creation of efficient combined energy-to-electrical converters and shows the prospects of this direction. The formulation of the problem and the correct selection of elements of hybrid devices are indicated. The issues of combining photoelectric converters with thermoelectric converters and micro hydroelectric power stations are discussed. The design of installations and the results of theoretical and experimental studies are presented.
Keywords: conversion, solar cell, thermoelement, microhydroelectric power station, energy, light radiation, heat, efficiency, design, operation